Comparing social reciprocity in preserved speech variant and typical Rett syndrome during the early years of life. (August 2015) - Townend, Gillian S.; Bartl-Pokorny, Katrin D.; Sigafoos, Jeff; Curfs, Leopold M.G.; Bölte, Sven; Poustka, Luise; Einspieler, Christa; Marschik, Peter B.
Highlights: Compares social reciprocity in typical Rett syndrome and the preserved speech variant. Utilizes retrospective video analysis to look at pre-regression behavior. Offers differing profiles of early social awareness in variants of Rett syndrome. Contributes toward fuller descriptive profiles for variants of Rett syndrome. Abstract: This study compared early markers of social reciprocity in children with typical Rett syndrome (RTT) and in those with the preserved speech variant (PSV) of RTT. Retrospective video analysis of 10 toddlers with typical RTT and five with PSV investigated participants' orientation to their name being called between the ages of 5 and 24 months, prior to their diagnosis. From analysis of the recordings two distinct profiles were apparent. Although response rate was higher in girls with typical RTT than PSV at 5 to 8 months this noticeably reversed from 9 to 12 months onwards. By two years of age there was a markedly higher rate and range of responses from girls with PSV. This study contributes to the delineation of different profiles for the variants of RTT.